Pengaruh Manajemen Laba, Dividen change dan Tax avoidance Terhadap Return Saham dengan Good Corporate Governance Sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2015 - Astuti, Intan Novia (Lembaga KITA, 2019)
The objective of the research was to find out and analyze the influence of profit management, dividend change and tax avoidance on stock return with institutional ownership as the moderating variable. This is causal associative research using quantitative data. This research used secondary data sourced from site www.idx.co.id, particularly the annual report of companies in 2011, 2012, 2013, 2014, and 2015. The population was all manufacturing companies listed on the Indonesian Stock Exchange in the period from 2011 until 2015 i.e. 49 companies. The whole population with observation years from 2011 until 2015 was taken as the samples; thus, there were 245 observations in the research. The data analysis employed multiple linear regression model, residual testing and classic assumption testing consisting of normality, multicollinearity, heteroscedasticity and autocorrelation testing. The results of the research demonstrated that (1) simultaneously profit management, dividend change, and tax avoidance had an influence of stock return; partially only dividend change had an influence on stock return while profit management and tax avoidance did not have any influence on stock return; (2) that institutional ownership could not moderate the influence of profit management on stock return, that institutional could not moderate the influence of dividend change on stock return, and institutional ownership could not moderate the influence of tax avoidance on stock return.Keywords: Profit Management, Dividend Change, Tax avoidance, Stock Return, Institutional Ownership